2010
DOI: 10.1037/a0017177
|View full text |Cite
|
Sign up to set email alerts
|

A test of motor (not executive) planning in developmental coordination disorder and autism.

Abstract: Grip selection tasks have been used to test "planning" in both autism and developmental coordination disorder (DCD). We differentiate between motor and executive planning and present a modified motor planning task. Participants grasped a cylinder in 1 of 2 orientations before turning it clockwise or anticlockwise. The rotation resulted in a comfortable final posture at the cost of a harder initial reaching action on 50% of trials. We hypothesized that grip selection would be dominated by motoric developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(121 citation statements)
references
References 32 publications
10
108
1
2
Order By: Relevance
“…Though it is unclear whether motor imagery deficits play a causal role in motor impairment in ADHD or are in fact a symptom of such impairment, an inability to accurately represent movements internally is likely to result in problems with motor planning and the efficient use of feedforward models of motor control (Blakemore et al, 2002;Flanagan et al, 2003). In DCD, this is reflected not only in motor imagery as it is here, but also in motor planning (van Swieten et al, 2010) and online movement control (Hyde & Wilson, 2011a, 2011b. It is critical therefore that clinically, motor skill assessments are included in assessments of children with ADHD and impairments are considered seriously, with interventions provided.…”
Section: Resultsmentioning
confidence: 98%
“…Though it is unclear whether motor imagery deficits play a causal role in motor impairment in ADHD or are in fact a symptom of such impairment, an inability to accurately represent movements internally is likely to result in problems with motor planning and the efficient use of feedforward models of motor control (Blakemore et al, 2002;Flanagan et al, 2003). In DCD, this is reflected not only in motor imagery as it is here, but also in motor planning (van Swieten et al, 2010) and online movement control (Hyde & Wilson, 2011a, 2011b. It is critical therefore that clinically, motor skill assessments are included in assessments of children with ADHD and impairments are considered seriously, with interventions provided.…”
Section: Resultsmentioning
confidence: 98%
“…In particular, problems with motor planning for end-state-comfort have been reported to occur more often in DCD [81,82]. Problems with sequencing and coordinating complex movement, referred to as ideomotor apraxia have also been found [80].…”
Section: Specific Mental Functionsmentioning
confidence: 99%
“…This is in line with evidence for impairments in visuospatial processing in DCD (see Wilson & McKenzie, 1998;Wilson, Ruddock, Smits-Engelsman, Polatajko & Blank, 2013, for meta-analyses). Finally, in tests of planning in children with DCD, both Pratt et al (2014) and van Swieten et al (2010) reported significantly more errors compared to controls in a task with significant motor demands, which involved planning arm movements to end in a comfortable position. On the other hand, Several methodological and interpretational difficulties arising from previous research into EF in DCD were addressed in the current study.…”
mentioning
confidence: 90%